Fado, urban popular song, and intangible heritage: perceptions of authenticity and emotions in TripAdvisor reviews - Carvalho, Inês (2023)
Intangible cultural heritage, such as music, often becomes the symbol of urban spaces. One example is fado, a music genre that originated in Lisbon, Portugal. With the increasing prominence of fado as a cultural heritage, an increasing number of tourists are attracted to fado shows. In this context, this study seeks to answer the following research question: “How do emotion and authenticity relate to visitors’ overall satisfaction in fado venues?”. Based on mixed methods research (descriptive statistics, inferential statistics, and content analysis), 2653 TripAdvisor reviews of four fado venues in Lisbon were analyzed. We conclude that although both authenticity and emotion are highly associated with overall satisfaction, lack of authenticity was not markedly associated with dissatisfaction. The most recent fado house is perceived as the most authentic one.